Synchronization Analysis of a Class of Neural Networks with Multiple Time Delays - Changyou Wang; Qiang Yang; Tao Jiang; Nan Li (Journal of Mathematics, 2021)
In this paper, we study the synchronization of a new fractional-order neural network with multiple delays. Based on the control theory of linear systems with multiple delays, we get the controller to analyse the synchronization of the system. In addition, a suitable Lyapunov function is constructed by using the theory of delay differential inequality, and some criteria ensuring the synchronization of delay fractional neural networks with Caputo derivatives are obtained. Finally, the accuracy of the method is verified by a numerical example.